Restauración psicológica y estrés percibido según el entorno de realización de ejercicio (2024)
The different daily dynamics experienced by human beings have increasingly evidenced the need to counteract adverse effects such as mental fatigue and high levels of stress, which is why the main objective of this study was to explain the influence of the exercise environment on psychological restoration and perceived stress in adults in Barranquilla. For this purpose, the methodology employed was quantitative, with a non-experimental and cross-sectional design. The sample consisted of 188 adults, selected by convenience, who exercised in outdoor parks (102) and in closed gyms (86). The Perceived Stress Scale (EEP-10) and the Restoration Outcome Scale (ROS) were used for data collection. The main findings indicated that exercise environments significantly influence psychological restoration and perceived stress. In addition, it showed that participants who exercised in indoor gyms reported higher levels of psychological restoration compared to those who exercised outdoors. Finally, natural environments, although less effective in terms of perceived psychological restoration, were found to provide greater benefits in stress reduction.